Patients’ perspectives and experiences concerning barriers to accessing information about bilateral prophylactic mastectomy - Glassey, R.; O'Connor, Moira; Ives, A.; Saunders, C.; kConFab Investigators; O'Sullivan, S.; Hardcastle, Sarah (Churchill Livingstone, 2018)
© 2018 Elsevier Ltd. Purpose: To explore the barriers and experiences of accessing information for women who have received genetic risk assessment/testing results for breast cancer (BC) and are considering a bilateral prophylactic mastectomy (BPM) and, exploring participants’ preferences concerning information and support needs. Methods: A qualitative retrospective study guided by interpretative phenomenological analysis was utilised. Semi-structured interviews were conducted with forty-six women who were either considering BPM or had already undergone the surgery. Results: Three themes identified barriers to accessing information; difficulties accessing information, inconsistent information and clinical focus/medicalized information. A fourth theme - preferences of information and support needs, identified three subthemes; these were, psychological support, clearly defined processes and photos of mastectomies/reconstruction surgeries. Conclusions: Barriers to accessing information appeared to be widespread. A lack of integrated services contributed to inconsistent information, and medicalized terminology/clinical focus of consultations further complicated understanding. Preferences for information include clearly defined processes, so women know the pathways after confirmation of familial BC risk. Clinical implications include a multidisciplinary team approach, and a protocol that reflects current practice.